Isomorphism of integrated reporting's sustainability embeddedness: evidence from Indonesian listed companies - Imanda Firmantyas Putri Pertiwi; Hadri Kusuma; Kumala Hadi; Johan Arifin; Ika Yoga; Auliya Zakky Fahma (Cogent Business & Management, 2022)
This study aimed to discover to what extent listed companies in Indonesia respond to the sustainability embeddedness of integrated reporting (SE of IR) as the world's latest reporting trend. Furthermore, this research also investigated the isomorphism predictors of the SE of IR adoption rate. The data was incorporated into the annual statements of 322 companies listed on the Indonesia Stock Exchange from 2014 to 2019. The panel data procedure employed 1932 observation. Descriptive statistics were used to answer the companies' responses to SE of IR adoption levels. Inferential statistics, including multivariate and univariate analysis, are conducted to discover the isomorphism predictors of SE of IR adoption. As the novelty of this research, the political connection proved to be an effective coercive isomorphism mechanism. Other variables that significantly influenced the adoption of IR are the board's professionalism and the company's participation in sustainability awards. Both variables represent normative isomorphism. In contrast, the parent company as the variable of mimetic isomorphism had no significant effect on SE of IR adoption.
Keywords: 650; coercive; institutional theory; integrated reporting; isomorphism; mimetic; normative; sustainability embeddedness